‘I just wanna see someone get knocked the fuck out’: Spectating affray on Facebook fight pages - Wood, Mark A. (Crime, Media, Culture: An International Journal, 2018)
Spurred by the advent of the Internet and the camera phone, in the early 21st century street fighting met the information superhighway. Today, one of the key vehicles accelerating this turn are Facebook fight pages: user-generated content aggregation pages that publicly host footage of street fights, and other forms of bare-knuckle violence on the popular social networking site. Drawing on observational data collected from five popular fight pages, and survey data from 205 fight page users, this article explores the different forms of bare-knuckle violence hosted on these online domains and their users’ motivations for viewing it. Through doing so, it examines eleven distinct modes of spectating bare-knuckle violence on fight pages: entertainment, consumptive deviance, righteous justice, amusement, self-affirmation, nostalgia, boredom alleviation, intrigue, self-defence training and risk awareness. Additionally, I argue that to understand these modes of spectating bare-knuckle violence, we have to address the codes of masculinity that underlie not only much of the violence hosted on fight pages, but also spectators’ readings of these events.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQxNjU5MDE2NjY3NDM3